2022
DOI: 10.1002/smll.202105499
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin and Super Strong UHMWPE Supported Composite Anion Exchange Membranes with Outstanding Fuel Cells Performance

Abstract: papers to make MEA after being immersed in 1 mol L −1 KOH for 24 h to be converted to OH − form. Finally, a single cell fuel test was operated on a fuel cell test station (850e Multi Range, Scribner Associates Co.), with humidified hydrogen and oxygen supplied, at 65 °C and 0.15 MPa backpressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 40 publications
(14 reference statements)
0
12
0
Order By: Relevance
“…As can be seen in Figure S6, the E a of QAPCE-1.4P is 14.44 kJ mol –1 , which suggests that less energy is required for the OH – transportation and a high ion conducting efficiency in QAPCE-1.4P. Furthermore, a comparison of the OH – conductivity of the as-prepared membranes with other AEMs reported in recent years is presented in Figure b. It can be found that QAPCE-1.4P has a higher OH – conductivity than other membranes in a similar IEC, indicating that the performance of AEMs can be enhanced by improving the phase separation of membranes via adjusting the hydrophilic–hydrophobic polarity. Meanwhile, the complexation of sodium ions and crown ether plays a role as the cationic groups (as confirmed in Figure S3) that is also helpful to enhance the electrochemical behaviors of AEMs.…”
Section: Resultsmentioning
confidence: 63%
“…As can be seen in Figure S6, the E a of QAPCE-1.4P is 14.44 kJ mol –1 , which suggests that less energy is required for the OH – transportation and a high ion conducting efficiency in QAPCE-1.4P. Furthermore, a comparison of the OH – conductivity of the as-prepared membranes with other AEMs reported in recent years is presented in Figure b. It can be found that QAPCE-1.4P has a higher OH – conductivity than other membranes in a similar IEC, indicating that the performance of AEMs can be enhanced by improving the phase separation of membranes via adjusting the hydrophilic–hydrophobic polarity. Meanwhile, the complexation of sodium ions and crown ether plays a role as the cationic groups (as confirmed in Figure S3) that is also helpful to enhance the electrochemical behaviors of AEMs.…”
Section: Resultsmentioning
confidence: 63%
“…5e. 12,13,[16][17][18]34,35,[40][41][42][43][44][45][46][47][48][49] It can be seen that our present AEMFCs display the best power density and durability among currently reported AEMFCs.…”
Section: The Performance Of Qabp-x-based Aemfcsmentioning
confidence: 96%
“…Some recent studies have demonstrated excellent performance improvement in AEMFCs using ultrathin membranes. For instance, Wei et al 12 achieved high-performance AEMFCs (power density of 1.04 W cm −2 ) based on an ultrathin reinforced composite membrane of 4 μm. Impressively, the polytetrafluoroethylene reinforced AEMs with a thickness of 10 μm fabricated by Kohl et al 13 with high ion exchange capacity (IEC) values (3.52 mmol g −1 ) can reach a high peak power density (PPD) of 3.21 W cm −2 .…”
Section: Introductionmentioning
confidence: 99%
“…Wei's group prepared an ultrathin (4–10 μm) reinforced composite membrane via in situ bulk polymerization. With minimal swelling behavior, the hydroxide conductivity reaches 105.9 mS cm −1 at an IEC value of 1.52 mmol g −1 [138] . C. Hu et al.…”
Section: The Stability Of Aemmentioning
confidence: 99%
“…With minimal swelling behavior, the hydroxide conductivity reaches 105.9 mS cm À 1 at an IEC value of 1.52 mmol g À 1 . [138] C. Hu et al used porous PE substrate and high-performance poly(aryl-coaryl piperidinium) to construct sandwich reinforced structure. Due to its superior mechanical properties, the novel AEM exhibits lowered swelling ratio from 60 % to 18.9 % at high IEC values of 2.4 mmol g À 1 and increased stability from 120 h to 360 h in fuel cell.…”
Section: Mechanical Stabilitymentioning
confidence: 99%